Integration of metagenomics‐metabolomics reveals specific signatures and functions of airway microbiota in mite‐sensitized childhood asthma. Issue 11 (13th July 2020) - Chiu, Chih‐Yung; Chou, Hsin‐Cheng; Chang, Lun‐Ching; Fan, Wen‐Lang; Dinh, Michael Cong Vinh; Kuo, Yu‐Lun; Chung, Wen‐Hung; Lai, Hsin‐Chih; Hsieh, Wen‐Ping; Su, Shih‐Chi
Abstract: Background: Childhood asthma is a multifactorial inflammatory condition of the airways, associated with specific changes in respiratory microbiome and circulating metabolome. Methods: To explore the functional capacity of asthmatic microbiome and its intricate connection with the host, we performed shotgun sequencing of airway microbiome and untargeted metabolomics profiling of serum samples in a cohort of children with mite‐sensitized asthma and non‐asthmatic controls. Results: We observed higher gene counts and sample‐to‐sample dissimilarities in asthmatic microbiomes, indicating a more heterogeneous community structure and functionality among the cases than in controls. Moreover, we identified airway microbial species linked to changes in circulating metabolites and IgE responses of the host, including a positive correlation between Prevotella sp oral taxon 306 and dimethylglycine that were both decreased in patients. Several control‐enriched species ( Eubacterium sulci, Prevotella pallens, and Prevotella sp oral taxon 306 ) were inversely correlated with total and allergen‐specific IgE levels. Genes related to microbial carbohydrate, amino acid, and lipid metabolism were differentially enriched, suggesting that changes in microbial metabolism may contribute to respiratory health in asthmatics. Pathway modules relevant to allergic responses were differentially abundant in asthmatic microbiome, such as enrichments for biofilm formation by Pseudomonas aeruginosa, membrane trafficking, histidine metabolism, and glycosaminoglycan degradation, and depletions for polycyclic aromatic hydrocarbon degradation. Further, we identified metagenomic and metabolomic markers (eg, Eubacterium sulci ) to discriminate cases from the non‐asthmatic controls. Conclusions: Our dual‐omics data reveal the connections between respiratory microbes and circulating metabolites perturbed in mite‐sensitized pediatric asthma, which may be of etiological and diagnostic implications. Abstract : This study demonstrates shotgun sequencing of airway microbiome and untargeted metabolomics profiling of serum samples in children with mite‐sensitized asthma and non‐asthmatic controls. Integrative analysis identifies specific airway dysbiosis at the species level and its associated functional shift in strong associations with circulating metabolites and IgE responses to mites. Overall, dual‐omics integration reveals microbe‐metabolite connections perturbed in mite‐sensitized pediatric asthma. Abbreviations: KEGG, Kyoto Encyclopedia of Genes and Genomes; AUC, area under the receiver operating characteristic curve